Nanoassemblies from Amphiphilic Sb Complexes Target Infection Sites in Models of Visceral and Cutaneous Leishmaniases - Juliane S. Lanza; Virginia M. R. Vallejos; Guilherme S. Ramos; Ana Carolina B. de Oliveira; Cynthia Demicheli; Luis Rivas; Sébastien Pomel; Philippe M. Loiseau; Frédéric Frézard (Pharmaceutics, 2022)
This work aims to evaluate whether nanoassemblies (NanoSb) made from antimony(V) complexes with octanoyl-N-methylglucamide (SbL8) or decanoyl-N-methylglucamide (SbL10) would effectively target the infection sites in visceral and cutaneous leishmaniases (VL and CL). NanoSb were investigated regarding stability at different pHs, accumulation of Sb in the macrophage host cell and liver, and in vitro and in vivo activities in models of leishmaniasis. The kinetic stability assay showed that NanoSb are stable at neutral pH, but release incorporated lipophilic substance after conformational change in media that mimic the gastric fluid and the parasitophorous vacuole. NanoSb promoted greater accumulation of Sb in macrophages and in the liver of mice after parenteral administration, when compared to conventional antimonial Glucantime®. SbL10 was much more active than Glucantime® against intramacrophage Leishmania amastigotes and less cytotoxic than SbL8 against macrophages. The in vitro SbL10 activity was further enhanced with co-incorporated miltefosine. NanoSb showed high antileishmanial activity in the L. donovani murine VL after parenteral administration and moderate activity in the L. amazonensis murine CL after topical treatment. This study supports the ability of NanoSb to effectively deliver a combination of Sb and co-incorporated drug to host cell and infected tissues, in a better way than Glucantime® does.